(untitled) (Research, Society and Development, 2021)
Objective: to analyze the number of cases of drug intoxication in the state of Maranhão between the years 2010 to 2020, through the intoxication data available in DATASUS. Methods: an ecological study with a quantitative approach, carried out from the analysis of data on notification of drug poisoning available in the system of the Information Technology Department of the Unified Health System - DATASUS, between the years 2010 to 2020. Results and discussion: between 2010 and 2020, 2,242 cases of drug poisoning were reported in the state of Maranhão, with the occurrence predominating among women. Regarding age group, the highest occurrence was among adults aged 20 to 39 years, followed by children aged 0 to 4 years. Final considerations: the state of Maranhão presented significant cases of drug intoxication during the analyzed period, especially in groups of people involving children and women. It emphasizes the need to create public health policies aimed at preventing these cases, as well as the engagement of health professionals so that cases of drug intoxication are notified, thus avoiding underreporting.